2017
DOI: 10.22159/ajpcr.2017.v10i5.17285
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic colonization of Staphylococcus aureus with intermediate resistance to vancomycin harboring vanB resistance gene

Abstract: Objective: Vancomycin has been used worldwide due to empirical therapy against methicillin-resistant Staphylococcus aureus infections. As a result a selective pressure that favors the outgrowth of vancomycin intermediate S. aureus clones will be created. This study was carried out to evaluate vancomycin resistance pattern of S. aureus in Jordan.Methods: A total of 1179 samples, including 566 (48%) from human and 613 (52%) from animals were examined for the presence of S. aureus using standard biochemical tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Besides, a recent study has shown that VISA growth rate is lower and that the cells harbor a thicker cell wall than those fully susceptible. 9 , 11 . Heterogeneous VISA (hVISA) show MICs in the susceptible range (≤ 2 μg/mL), but they contain a sub-population that expresses a resistant phenotype 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a recent study has shown that VISA growth rate is lower and that the cells harbor a thicker cell wall than those fully susceptible. 9 , 11 . Heterogeneous VISA (hVISA) show MICs in the susceptible range (≤ 2 μg/mL), but they contain a sub-population that expresses a resistant phenotype 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the current study were an approach to the researcher's findings [13]; in Diyala in Iraq in a study including 100 isolation from E. coli bacteria to detect their susceptibility to antibiotic resistance, the results show that 22% of isolates were of multiple resistance while the resistance to ampicillin was 100%; the researcher is likely to cause resistance to the use of antibiotics for long-term treatment [14]. The reason for tetracycline resistance in E. coli bacteria is the presence of flow pump efflux pumps of major facilitator super family (MFS) flow pumps that expel anti-tetracycline to the outside and do not expel minocycline, the protein that is encoded by the tetB gene only for it.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 7 , 19 ] proposed that brain infusion or oral administration of propionic acid (PPA) to rat pups could induce many of the biochemical characteristics observed in individuals with autism. Moreover, histopathological changes, such as neuronal loss, hyaline bodies, and astrogliosis, together with several behavioral traits such as hyperactivity, impaired social interaction, reduced exploratory activity, and increased repetitive behaviors, have been recorded [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%